Nature for whom? How type of beneficiary influences the effectiveness of conservation outreach messages. (December 2018) - Batavia, Chelsea; Bruskotter, Jeremy T.; Jones, Julia A.; Vucetich, John A.; Gosnell, Hannah; Nelson, Michael Paul
Abstract: In recent years the conservation community has engaged in debate over value in nonhuman nature, especially as it relates to motivations for conservation. Many have expressed the assumption that more people are willing to support conservation when emphasis is placed on the human benefits of nonhuman nature, rather than the value of nonhuman nature for its own sake. To test this assumption, we designed an online survey investigating how the type of beneficiary (human, nonhuman, or both) depicted in outreach messages affects two metrics of support: attitudes toward the message and donations for a conservation organization. Each respondent viewed one message highlighting humans, nonhumans, or both as conservation beneficiaries. Predicting that the effect of beneficiary type would depend partially on individual differences, we also measured respondents' moral inclusivity, i.e., the values and beliefs they hold with regard to human and various nonhuman entities. Although beneficiary type did not affect attitudes, we report several key findings for donation. Compared to messages depicting only nonhuman beneficiaries, messages depicting only human beneficiaries were associated with lower likelihood of donation overall and, among less morally inclusive respondents, lower donation amounts. At the same time, messages depicting both human and nonhuman beneficiaries were not associated with more positive donation outcomes than messages depicting only nonhuman beneficiaries. Our results suggest that highlighting humans as conservation beneficiaries may not most effectively generate social support for conservation. Messages advocating the protection of nonhuman nature for its own sake may produce the most consistently positive donation outcomes. Highlights: Tested messages presenting human, nonhuman, or combined conservation beneficiaries All three message types elicited equally positive attitudinal responses. Nonhuman messages were more likely to elicit a donation than human messages. Least morally inclusive respondents donated more to nonhuman than human messages. No evidence "nature for people" is most effective conservation outreach strategy.